Multiorgan‐on‐a‐chip for realization of gut‐skin axis. Issue 9 (10th July 2022) - Lee, Hye Ri; Sung, Jong Hwan
Abstract: The concept of physiological link between the gut and the skin, known as the gut‐skin axis, has been gaining more evidence recently. Although experimental data from animal and human studies support the existence of the gut‐skin axis, in vitro model platforms that can test the hypothesis are lacking. Organ‐on‐a‐chip offers the possibility of connecting different tissues and recapitulating interactions between them. In this study, we report a multiorgan chip that can capture the basic interorgan communication between the gut and the skin. Its modular design enables separate culture and differentiation of the gut and skin tissues, and after assembly the two organs are connected via microfluidic channels than enables perfusion and mass transfer. We showed that the impairment of the gut barrier function exacerbated the adverse effect of fatty acids on skin cells, with decreased viability, increased level of cytokine secretion and human beta defensin‐2 (hBD‐2), an inflammatory dermal disease marker. Based on these results, we believe that our multiorgan chip can be a novel in vitro platform for recapitulating complex mechanisms underlying the gut‐skin axis.